Learning styles and their relationship to academic achievement in freshmen students of dentistry - Ortiz-Fernández, Lita (2015)
This study aimed to identify learning styles preference and their relationship to academic achievement in freshman students. Methodology: Honey-Alonso Learning Styles (CHAEA) questionnaire was used; and evaluation report academic of the freshman students as evidence of their performance 48 student volunteers who participated in the mentoring program; mentor teachers and students were trained. Results: The 32% of freshman students come from public educational institutions and from 78% private; the average age is 19 years old and SD + -2.73. It was found that the theoretical learning style prevails (35, 4%), followed by active learning style (25%) with a moderate preference. Learning styles preference were compared at the beginning and at the end of the academic year, it was founded differences in active, theoretical and pragmatic learning styles; also it was founded relation between reflexive, theoretical and pragmatic learning styles with academic performance of the freshman students. The reflexive learning style has been very below average, it is necessary to motivate them in order to strengthen autonomy in student learning, balancing theoretical style as the active, in addition to being immersed in an institution that provides health services , contact live with another human being , one must be cautious , discreet and thorough , as well as know how to observe and listen to deliver better care to patients, as have the ability of self-education is the most appropriate health professional.